PROMOTING SOCIAL WELFARE FOR SMES: A CASE STUDY IN MEDAN TEMBUNG - Dedy Lazuardi; Ihdina Gustina; Muammar Rinaldi; Irma Herliza Rizki (RADJA PUBLIKA, 2025)
This study evaluates the economic welfare of respondents in the Medan Tembung region with a focus on poverty levels and their implications for the economic conditions. The research analyzes factors such as the number of dependents, monthly income, access to basic services, and market conditions to understand their impact. The findings indicate that the number of dependents and monthly income significantly affect respondents' financial stability, with those having higher dependents and lower income experiencing greater economic pressure. The balance between income and expenditure is also a concern, with many respondents facing financial deficits. Access to basic services such as health insurance (BPJS) and education plays a crucial role in maintaining financial stability, although some respondents still lack full access to these services. Market instability, especially rising prices of essential goods, directly impacts respondents' economic conditions. Protecting price stability is key to safeguarding community welfare. Appropriate policy measures are needed to enhance economic welfare in Medan Tembung, including the development of financial education programs and price stabilization policies. This research provides a deep understanding of the economic challenges faced by respondents in this area and highlights the need for effective policy interventions to improve welfare and reduce economic disparities.